Galectin-3: A Friend but Not a Foe during Trypanosoma cruzi Experimental Infection - da Silva, Aline A.; Teixeira, Thaise L.; Teixeira, Samuel C.; Machado, Fabrício C.; dos Santos, Marlus A.; Tomiosso, Tatiana C.; Tavares, Paula C. B.; Brígido, Rebecca T. e Silva; Martins, Flávia Alves; Silva, Nadjania S. de Lira; Rodrigues, Cassiano C.; Roque-Barreira, Maria C.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Trypanosoma cruzi interacts with host cells, including cardiomyocytes, and induces the production of cytokines, chemokines, metalloproteinases, and glycan-binding proteins. Among the glycan-binding proteins is Galectin-3 (Gal-3), which is upregulated after T. cruzi infection. Gal-3 is a member of the lectin family with affinity for β-galactose containing molecules; it can be found in both the nucleus and the cytoplasm and can be either membrane-associated or secreted. This lectin is involved in several immunoregulatory and parasite infection process. Here, we explored the consequences of Gal-3 deficiency during acute and chronic T. cruzi experimental infection. Our results demonstrated that lack of Gal-3 enhanced in vitro replication of intracellular parasites, increased in vivo systemic parasitaemia, and reduced leukocyte recruitment. Moreover, we observed decreased secretion of pro-inflammatory cytokines in spleen and heart of infected Gal-3 knockout mice. Lack of Gal-3 also led to elevated mast cell recruitment and fibrosis of heart tissue. In conclusion, galectin-3 expression plays a pivotal role in controlling T. cruzi infection, preventing heart damage and fibrosis.